Cryopreservable three-dimensional spheroid culture for ready-to-use systems - Truong, Thuy Trang; Lee, Yu Bin; Park, Kyoung Hwan; Shim, Hye-Eun; Song, Jin Jung; Kim, Hyung-Sun; Hwang, Jeong Ho; Kang, Sun-Woong; Huh, Kang Moo (The Korean journal of chemical engineering, 2023)
Three-dimensional (3D) spheroid culture has applications in many fields as spheroids closely recapitulate physiological conditions. However, spheroid culture and maintenance are time-consuming and unsuitable for urgent situations; therefore, appropriate cryopreservation methods for spheroids are required for their use in an on-demand and ready-to-use manner. We hypothesized that the feasibility of a ready-to-use system relies on diffusion of the preservation solution within spheroids; we thus evaluated the effects of spheroid-forming parameters, such as cell number and culture period, on spheroid viability and functionality. Long-term spheroid culture for seven days interfered with penetration of the cryopreservation solution as it caused cell condensation and extracellular matrix (ECM) secretion, as well as low viability and migratory activity upon replating after storage. However, ready-to-use spheroids, which were cultured for one day and then cryopreserved, showed viability and migration similar to those of non-cryopreserved spheroids, confirming that a short incubation period was suitable for this system. The chondrocyte-based ready-to-use spheroid system designed in this study can be easily applied to regenerative medicine applications that require a large number of cells in the future and can provide information for applying the ready-to-use spheroid system to various cell types.